The Use of Artificial Intelligence in Improving Students’ Speaking Skills - Pratama, Rizky Mirani Desi; Hastuti, Dwi Puji (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
In today’s globalized world, English language skills are essential for effective communication and opening up access to wider opportunities. Unfortunately, many junior high school students, especially in areas such as West Jakarta, face challenges in developing adequate speaking skills due to limited opportunities for interaction and practice. The learning methods used in schools often fail to provide the interactive and engaging environment needed to master speaking skills. To address these challenges, educators are increasingly turning to technological innovations, such as Artificial Intelligence (AI), to enhance the language learning experience. This study aims to determine the effectiveness of use artificial intelligence (AI) in learning English especially in improving students' speaking skills. Research methods that used are mixed-methods, combining quantitative and qualitative method. The research participants consisted of 30 junior high school students in the West Jakarta area. In this study, researchers used AI as a method of learning English, especially speaking skills. This research applies AI platforms, namely Canva and Vocaroo. The research results show there is a significant increase in speaking skills, after using AI. These findings support that the use of AI is effective in learning English, especially speaking skills. From the analysis carried out, it can be seen that the output Sig = 0.00. That is, the mean pre-test and post-test are different. So, it can be concluded that the application of Canva and Vocaroo media is effective in improving students' speaking skills and learning outcomes in General Conversation courses. The effectiveness of learning with Canva and Vocaroo media can also be seen from the average pre-test score of 67.92 and post-test of 85.84 which shows that learning outcomes have increased. Observations made in the learning process using Canva and Vocaroo media showed that the average student's speaking ability was in the good category and improved